Principles of ECONOMICS - Mankiw, N. Gregory (Cengage Learning, 2024)
Gain a strong foundation in economics with today's most popular economics text, trusted by students like you worldwide -- Mankiw's PRINCIPLES OF ECONOMICS, 10E. Using a clear, inviting writing style, this edition focuses exclusively on content to help you better understand the world and economy in which you live. You become a more astute participant in today's economic environment as you learn the potential and limits of economic policy. The latest examples and learning features clarify and bring economic principles to life as author Gregory Mankiw puts himself in the position of someone seeing economics for the first time. Dr. Mankiw's goal is to emphasize the material you will find most relevant and interesting as you study economics. MindTap digital resources, Aplia digital homework solution and author videos are also available to help you further master key economic principles.